Improving the Quality of Character Education at the Elementary School Level - Ifnuari, Moh. Reza (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Character education is an effort to strengthen and improve the nation’s moral or ethical values, especially students who will become the nation’s next generation and the end for the success of the nation’s success with noble character, especially in the golden age of elementary school children’s education. The state is responsible for that with the noble values ​​possessed by our ancestors before, where these values ​​are a way to unite the diversity of the Indonesian nation, from ethnicity, race and religion. Efforts to improve character education in schools is one way to anticipate and minimize the nation’s moral decline which is a problem in the world of education, especially in Indonesia. This study aims to identify the management of character education in schools. This research is library research. The Literature Review was used to obtain articles from online databases that were relevant to the management of character education in schools from 2015 to 2020. The results of the 22 articles reviewed were an increase in character education that required collaboration between teachers, all school members, parents, the community, so that what has been determined can be realized, namely students who have and instill moral values ​​in life.